Screening and brief intervention for alcohol problems in Dr George Mukhari Hospital out-patients in Gauteng, South Africa: a single-blinded randomized controlled trial protocol - Pengpid Supa; Peltzer Karl; Skaal Linda; van der Heever Hendry; Van Hal Guido (BMC, 2012)
Abstract Background For alcohol drinkers in South Africa it has been found that annual consumption per drinker is among the highest in the world. High prevalence rates of hazardous and harmful alcohol use have also been found in a hospital out-patient setting in South Africa. Hospital settings are a particularly valuable point of contact for the delivery of brief interventions because of the large access to patient populations each year. With this in mind, the primary purpose of this randomized controlled trial is to provide screening for alcohol misuse and to test the efficacy of brief interventions in reducing alcohol intake among hospital out-patients in South Africa. Methods/Design The study design for this efficacy study is a randomised controlled trial with 6- and 12-month follow-ups to examine the effects of a brief alcohol intervention to reduce alcohol use by problem drinkers in a hospital setting. The unit of randomisation is the individual out-patient identified as a medium risk drinker attending Dr George Mukhari Hospital. Out-patients will be screened for alcohol problems, and those identified as medium risk drinkers will be randomized into an experimental or control group. The experimental group will receive one brief counselling session on alcohol risk reduction, while the control group will receive a health education leaflet. Discussion The trial will evaluate the impact of alcohol screening and brief interventions for patients with alcohol problems in a hospital out-patient setting in South Africa. The findings will impact public health and will enable the health ministry to formulate policy related to brief alcohol interventions, which will result in reduction in alcohol use. Trial registration PACTR201110000319392